2021
DOI: 10.1177/1358863x211006470
|View full text |Cite
|
Sign up to set email alerts
|

Arterial aneurysm and dissection with systemic vascular endothelial growth factor inhibitors: A review of cases reported to the FDA Adverse Event Reporting System and published in the literature

Abstract: The US Food and Drug Administration (FDA) has approved multiple systemic vascular endothelial growth factor (VEGF) inhibitors since 2004 to treat various malignancies. Inhibition of the VEGF signaling pathway can result in impairment of vascular wall integrity through medial degeneration and endothelial dysfunction, potentially resulting in arterial (including aortic) aneurysm/dissection. We performed a postmarketing review to evaluate arterial aneurysm/dissection as a potential safety risk for patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“… 5 A similar study by Cheng et al reviewed the U.S. Food and Drug Administration Adverse Event Reporting System to identify 240 post‐market reports of arterial aneurysm or dissection associated with VEGF inhibitor with a median onset of 94 days and a fatality rate of 22%. 6 …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“… 5 A similar study by Cheng et al reviewed the U.S. Food and Drug Administration Adverse Event Reporting System to identify 240 post‐market reports of arterial aneurysm or dissection associated with VEGF inhibitor with a median onset of 94 days and a fatality rate of 22%. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al have also identified 20 published case reports of patients developing an arterial aneurysm or dissection while on VEGF inhibitors but to our knowledge there are no reports on such adverse events for patients solely treated with pazopanib. 6 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations